Comment: Kolnai's Disgust. (July 2014) - Korsmeyer, Carolyn; Smith, Barry
In The Meaning of Disgust (2011), Colin McGinn employs elements of the phenomenological theory of disgust advanced by Aurel Kolnai in 1929. Kolnai's treatment of what he calls "material" disgust and of its primary elicitors—putrefying organic matter, bodily wastes and secretions, sticky contaminants, vermin—anticipates more recent scientific treatments of this emotion as a mode of protective recoil. While Nina Strohminger (2014) charges McGinn with neglecting such scientific studies, we here attempt to show how Kolnai goes beyond experimental findings in his careful description of the phenomenological differences between disgust and other emotions of forceful disapproval.